Farming Systems Approach For Identifying R and D Options For Enhancing Income and Sustainability in Kafa-Sheka Zone of Ethiopia - Shalander Kumar, Francis Baah, Efrain A. Pozo, Taya Kufa, Africa Zeleke; Julius Okwadi (Indian Journal of Extension Education, 2022)
This study was conducted in Gimbo Woreda of Kafa-Sheka Zone (KSZ), Ethiopia with the aim to identify and analyse the farming systems and, analyse and prioritise research and development (R & D) options for enhancing income and sustainability of farming systems. The study area was classified for enhancing income and sustainability of farming systems. The study area was classfied into three zones namely, ’forest’, ’transition’ and ’deforested’ zones based on the "scale of deforestation". Consequently four farming systems were identified. The study envisaged a movement of the farming systems towards on that is based on coffee, a high income generating tree crop that also protects the environment. In the light of constraints and opportunities several R and D options were identified and prioritised.